A Comparison of Chinese and Indian Solar Theories in the Sui and Early Tang Periods (Seventh–Eighth Centuries c.e.). (November 2018) - Tang, Quan; Qu, Anjing
The Sovereign Pole System ( Huang ji li 皇極曆, a.d. 600) is the first Chinese astronomical system to include a solar equation table for calculating the motion of the Sun. From then on, each Chinese system took the solar equation of centre into consideration. Some scholars have argued that Chinese solar theory in the Sui and Tang dynasties was developed independently by Chinese astronomers. However, other scholars have speculated that this theory was ultimately influenced by Babylonian astronomy, through the medium of Indian astronomy. In this paper, we compare Chinese solar theory in the Sui and early Tang periods with Indian solar theory in the sixth century. First, we discuss the content, meaning, and accuracy of the solar equation tables in the Sovereign Pole System, the Great Patrimony System ( Da ye li 大業曆, a.d. 607), and the Great Expansion System ( Dan yan li 大衍曆, a.d. 727), three representative Chinese systems of the Sui and early Tang periods. Then, we discuss the speed of the Sun, the accuracy of the solar equation of centre, and the difference between the motions of the true Sun and mean Sun in the Vāsiṣṭha Siddhānta, Pauliśa Siddhānta, and Romaka Siddhānta, three Indian astronomical works collected in the Pañcasiddhāntikā in the sixth century. Finally, we discuss the similarities and differences between Indian and Chinese solar theories in the Sui and early Tang periods. The results show that while Chinese solar theory in the Sui and early Tang periods was very similar to Indian solar theory in the sixth century, Indian astronomers had a more sophisticated view of solar theory than their Chinese contemporaries, both in relation to the difference between the mean Sun and true Sun and in the selection of the longitude of perigee of the Sun. At the same time, we must note that the influence of Indian solar theory on Chinese solar theory was very limited, even if Chinese solar theory in the Sui and Tang dynasties was possibly influenced by Indian solar theory.